Bioactive deoxypreussomerins and dimeric naphthoquinones from Diospyros ehretioides fruits: Deoxypreussomerins may not be plant metabolites but may be from fungal epiphytes or endophytes - Areerat Prajoubklang (2018)
Deoxypreussomerin derivatives, palmarumycins JC1 (1) and JC2 (2), and two dimeric naphthoquinones, isodiospyrin (3) and its new derivative isodiospyrol A (4), were isolated from dried fruits of Diospyros ehretioides. Structures of the isolated compounds were elucidated by spectroscopic analyses. Palmarumycins were not found in the extract of freshly collected fruits; however, they were present in dried fruit extract. The absence of palmarumycins in fresh fruits of D. ehretioides, together with the chemotaxonomic point of view, we proposed that palmarumycins JC1 (1) and JC2 (2) are more likely to be fungal metabolites, i.e., endophytes or epiphytes. The isolation of palmarumycins 1 and 2 from dried D. ehretioides fruits could be reproducible; both plant samples collected in the years 2002 and 2004 provided the same result, and, therefore, symbiont fungal strains should be specific to the plant host, D. ehretioides, and they can grow on the fruits during drying the sample. Palmarumycin JC1 (1) did not exhibit antimalarial, antifungal, antimycobacterial, and cytotoxic activities. Palmarumycin JC2 (2) exhibited antimalarial (IC50 4.5 μg/ml), antifungal (IC50 12.5 μg/ml), antimycobacterial (MIC 6.25 μg/ml), and cytotoxic (IC50 11.0 μg/ml for NCI-H187 cell line) activities. In our bioassay systems, isodiospyrin (3) did not exhibit antimycobacterial, antifungal, antimalarial, and cytotoxic activities. Isodiospyrol A (4) exhibited antimalarial (IC50 2.7 μg/ml) and antimycobacterial (MIC 50 μg/ml) activities, but was inactive towards Candida albicans. Compound 4 also exhibited cytotoxicity against BC cells (IC50 12.3 μg/ml), but not towards KB and Vero cell lines. © 2005 Verlag Helvetica Chimica Acta AG, Zürich.